Urban Transport and CO2 Emissions : Some Evidence from Chinese Cities - Darido, Georges; Torres-Montoya, Mariana; Mehndiratta, Shomik (World Bank, Washington, DC, 2014)
This working paper provides a bottom-up estimate of energy use and Green-House Gas (GHG) emissions for the transport sector based on data available at the city and municipal levels. For urban transport in China, GHG emissions primarily consist of carbon dioxide (CO2), so these terms are used interchangeably. Energy use and CO2 emissions are also highly correlated based on the predominance of fossil fuels in transport. A database of self-reported indicators was developed and verified for the fourteen participating cities of the China World Bank-Global Environment Facility (GEF) Urban Transport Partnership Program. Other supplemental sources were also used to enrich the dataset for urban transport and energy analysis, namely the most recent China City Statistical Yearbooks. Beijing and Shanghai were also included where data was available from existing studies given their relevance in broad comparison of Chinese cities. Section two discusses the general demographic and economic trends in the sample of cities that may be influencing the sector. Section three points to stylized facts about the most relevant urban transport demand, supply and performance characteristics in recent years and suggests how they may be driving energy consumption and GHG emissions. Section four is the analysis and forecast of energy use and GHG emissions using the urban transport drivers identified. Finally, general conclusions and next steps are suggested in section five, as well as additional details on the data, methodology, definitions, and a map of China with the seventeen selected cities in the annexes.